Assessing the role of key genes involved in the reproductive success of the honey bee parasite Varroa destructor - Muntaabski, Irina; Salvador, Ricardo; Russo, Romina Maria; Wulff, Juan Pedro; Landi, Lucas; Liendo, María Clara; Lanzavecchia, Silvia Beatriz; Scannapieco, Alejandra Carla (BioMed Central, 2025)
The ectoparasite Varroa destructor is the primary global threat to the western honey bee, Apis mellifera. Growing resistance to acaricide-based treatments has spurred interest in alternative control strategies. In this study, we employed a novel and efficient dsRNA delivery method to explore the potential of RNA interference (RNAi)-based approaches for Varroa control in honey bee colonies. We assessed the effects of silencing six target genes (ptch1, ap-1, larp6, chisal, vg1, and vg6) on mite mortality and reproduction through a semi-field experiment. Gene expression analysis revealed significantly reduced transcript levels in mites treated with dsRNA compared to dsGFP controls, with knockdown efficiencies ranging from 88.6% to 97.2%. Silencing of ptch1, ap-1, and vg1 genes resulted in a significant increase in mite infertility, aligning with their known roles in oocyte maturation and embryogenesis. Additionally, silencing of chisal, previously described as essential for effective Varroa feeding, led to a marked increase in mite mortality. These results highlight promising gene targets for RNAi-based Varroa control strategies. Furthermore, our study provides new insights into the molecular pathways involved in mite reproduction and survival, including Wnt, c-Jun N-terminal kinase, Hedgehog, and apoptosis, paving the way for the development of more effective biotechnological control tools.